Identification of Petitot's Riviere La Ronciere-le Noury - Fraser, J.K. (ARCTIC, 1952)
Contains a study of explorations in the Horton and Hornaday River regions of northern Mackenzie District. Evidence is presented to suggest that the river discovered and mapped (excepting lower reaches) by the Oblate missionary Emile Petitot in 1868 is identical with the Hornaday. The latter, discovered by A.J. Stone in 1900 was explored only near its effluence into Darnley Bay. Recent mapping from aerial photographs show the source of the Hornaday (68 40 N, 120 20 W) and features of its course as similar to those recorded for La Ronciere-le Noury by Petitot in his Geographie de l'Athabaskaw-Mackenzie.1875.(Arctic Bibliography, No. 13406).